Padrão de formação familiar em diferentes grupos religiosos no Brasil - Ingrid Gomes Dias (2015)
Brazil has gone through important transformations in the process of family formation, which in this study refers to the beginning of a family starting from the union of a couple. An increase in the proportion of consensual unions has been observed, whereas the age it starts remains relatively precocious. Another important change refers to the religious context which shows a growth in the evangelic religions. The religious overview may be an important element for the family formation, which in this study refers to the chance of composing a union, the kind of union and the choice of spouse. This is due to the fact that religions influence the believers life, shaping their behavior through its mechanisms. The first sought to analyze the association between the Catholic and Evangelic religions as well as the pattern for the family formation using representative data from the 2010 census for women between 20 and 29 years old in Brazil. The latter proposed to investigate whether religion had influenced in any way the family formation and which were the main mechanisms of the religion influence based on data derived from thorough interviews that took place in the municipality of Viçosa, in the State of Minas Gerais, with Catholic and Pentecostal Evangelic women in the ages of 20 to 29, as well as ministers and priests. The quantitative results showed that the evangelic, especially the Pentecostal, have a differentiated patter of family formation, happening at a younger age at the time of the union, with a bigger chance of being in a formal union and higher rate of religious endogamy. The qualitative results revealed that the Pentecostal Churches present all the mechanisms of religious influence reported by Smith (2003) in his theory, whereas the Catholic Churches did not report sanctions mechanisms and network closure in the religious context, only family supervision. The data also indicate that the interviewed evangelic women present a more conservative and strict behavior regarding questions such as virginity, formal union and spouse choice (religious endogamy), a result of a bigger emphasis from the church to the norms and religious sanctions.